Lebanon : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses findings of the assessment of Lebanon's financial system. Lebanon has maintained financial stability for the last quarter century during repeated shocks and challenges. Over time, macroeconomic and financial vulnerabilities have accumulated. Although central bank policies have helped to maintain confidence, fiscal adjustment is needed to reduce risks to financial stability. The banking system has thus far proven resilient to domestic shocks and regional turmoil, but the materialization of severe shocks could expose vulnerabilities. Significant progress has been made to further strengthen Lebanon's financial integrity framework, with some scope for improvement remaining.